EPISTEMIC DECOLONIZATION OF AFRICAN HISTORIOGRAPHY IN AHMADOU KOUROUMA’S WAITING FOR THE WILD BEASTS TO VOTE - SAI, Iorvaa Peverga (International Journal of Arts, Languages, Linguistics and Literary Studies, 2026)
Epistemic decolonization of knowledge in Africa is a clarion call that beckons at African scholars in all disciplines. The African literature, especially the novel is highly committed to this engagement. Ahmadou Kourouma’s novel Waiting for the wild Beasts to Vote provides a springboard for analysis of African historiography. Employing an interdisciplinary methodology that combines literary criticism, historical analysis, and postcolonial theory, this article analysis how Kourouma reimagines African history by challenging Eurocentric narratives. The central problem addressed is the marginalization of African perspectives within dominant historical discourses, which have often distorted or silenced the continent’s historical experiences. In addition, the major thrust of the paper is to fill in the research gap in the scholarly exploration of how African literary narratives serve as tools for reconstructing a decolonized historiography. To this effect, the study highlights the role of the griot-narrator in Kourouma’s novel as a medium for reclaiming African culture, history and civilisation. In our findings, it is noted that Kourouma’s work not only deconstructs colonial historical accounts but also critiques post-independence authoritarianism in Africa, offering a nuanced perspective on the continent’s historical trajectory. The paper recommends a continuous systematic integration of African literary texts into historiographical studies to broaden understanding of African history. Furthermore, it advocates for the recognition of oral traditions as legitimate sources for reconstructing and interpreting African pasts, thus contributing to a more inclusive and decolonized historical discourse.